(untitled) (World Science, 2021)
Purpose of this of this work is to determine the gender characteristics of male and female athletes involved in complex coordination sports. The study involved 237 male and female athletes. A group of complex coordination sports was considered from the point of view of their influence on the formation of gender identity and gender similarities and differences were revealed in athletes and athletes specializing in figure skating, artistic and rhythmic gymnastics, synchronized swimming, rowing slalom, archery, kettlebell lifting and other difficult coordination sports. Among young men, the ratio of masculine and androgynous was 45 and 55%, respectively; among girls, 53 and 47%; among certain sports among young men, masculine athletes were found in kettlebell lifting 53% and sports acrobatics and sports ballroom dancing 45% each, and androgynous in modern dances 80 %. Among girls, masculine athletes, in total aesthetic group gymnastics is 67%, artistic gymnastics is 64%, synchronized swimming is 63% and kettlebell lifting is 61%. The similarities and differences between masculine and androgynous young men and women who specialize in complex coordination sports in relation to their personal qualities have been clarified. Personal identity is formed throughout life and sports activity is one of the factors that influences its formation. When analyzing the personal qualities of masculine and androgynous young men and masculine and androgynous women, more similarities were found between them than differences: among male athletes, the factors of rigidity - sensitivity, credulity - suspiciousness, and among female athletes, according to factors, restraint - expressiveness and self-confidence – anxiety.